ASME 2005 Internal Combustion Engine Division Fall Technical Conference (ICEF2005) 2005
DOI: 10.1115/icef2005-1325
|View full text |Cite
|
Sign up to set email alerts
|

Development of Advanced Laser Ignition System for Stationary Natural Gas Reciprocating Engines

Abstract: Laser ignition is considered the prime alternative to conventional coil based ignition for improving efficiency and simultaneously reducing NOx emissions in lean-burn natural gas fired stationary reciprocating engines. In this paper, Argonne’s efforts towards the development of a viable laser ignition system are presented. The relative merits of various implementation strategies for laser based ignition are discussed. Finally, the performance improvements required for some of the components for successful fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Weinrotter, Herdin et al [34] have tried to develop a split system wherein a long laser pulse from a pump laser is transmitted through a optical fiber to end pump a laser gain medium equipped with a saturable absorber installed in the spark plug well of the engine. Bihari et al through their attempts found it difficult to transmit high-power laser pulses through optical fibers and have embarked in developing a system that uses free-space transmission [31]. Recently, Taira et al [35,36] have successfully demonstrated microlaser ignition systems, by using new age lasing materials called optical ceramics, and by using pulse trains of low-energy pulses to ignite instead of a single high-energy laser pulse.…”
Section: Laser Ignitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weinrotter, Herdin et al [34] have tried to develop a split system wherein a long laser pulse from a pump laser is transmitted through a optical fiber to end pump a laser gain medium equipped with a saturable absorber installed in the spark plug well of the engine. Bihari et al through their attempts found it difficult to transmit high-power laser pulses through optical fibers and have embarked in developing a system that uses free-space transmission [31]. Recently, Taira et al [35,36] have successfully demonstrated microlaser ignition systems, by using new age lasing materials called optical ceramics, and by using pulse trains of low-energy pulses to ignite instead of a single high-energy laser pulse.…”
Section: Laser Ignitionmentioning
confidence: 99%
“…[22] Laser ignition tests performed in natural gas fueled single-cylinder engines have shown (i) shorter ignition delays, (ii) accelerated rates of combustion, and (iii) lean ignition limit extensions. However, as shown in Figure 20, the most significant advantage is the fact that laser ignition can result in NOx reductions up to 70% for a given engine efficiency, or alternately up to 3% point improvement in efficiency for a given NOx level [31]. The associated cost savings due to reduced fuel consumption, and avoidance of expensive after treatment systems, have provided an impetus for the development of practical laser ignition systems.…”
Section: Laser Ignitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, pilot ignition, which uses small diesel sprays as the ignition sources, offers the advantages of multiple ignition centres and higher energy densities compared with conventional spark ignition. Gebert et al [9] showed that the energy associated with a pilot diesel spray volume of 1 mm 3 is approximately two orders of magnitude greater than the energy provided by a spark. Therefore, the quality of ignition is better with diesel pilot ignition, and spatially dispersed, multiple-ignition centres lead to faster burn rates compared to singlepoint ignition sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge with employing natural gas as an engine fuel stems from the fact that it is primarily composed of methane, which is very difficult to ignite. Several ignition strategies including lean-burn spark ignition [1], laser ignition [2,3], and pilot ignition [4][5][6][7][8] have been utilized to increase efficiencies and to decrease emissions from natural-gas engines. Of these, pilot ignition, which uses small diesel sprays as the ignition sources, offers the advantages of multiple ignition centres and higher energy densities compared with conventional spark ignition.…”
Section: Introductionmentioning
confidence: 99%